Agricultural Land Use Mapping Analysis Using the Geographic Information System in Temu Village - Chintya Giba Alvia Burhanuddin; Yustina Rada; Erwianta Gustial Radjah (Yayasan Kita Menulis, 2024)
The agricultural sector remains a significant source of income for the people of East Sumba, particularly in Temu Village, Kanatang District, which spans 46.50 km². In Temu Village, a large portion of the population engages in farming and gardening, utilizing agricultural land that includes rice fields, fields, and plantations. Analyzing the current use of this land is crucial for predicting agricultural yields and proposing optimal land use strategies to ensure sufficient local food production. However, the distribution of agricultural land has not been thoroughly mapped, leaving gaps in information regarding the location and potential of these lands. This research aims to map the agricultural potential of Temu Village using Geographic Information System (GIS) technology through overlay and scoring methods, resulting in informative land use maps. The findings reveal that fields dominate the agricultural landscape with 1.648903 km² or 81.10% of the total agricultural land, highlighting the primary focus on field crops. Rice fields cover 0.270512 km² or 13.30%, while gardens occupy the smallest area of 0.113825 km² or 5.60%. These results demonstrate the potential for effective geographical management of plantations, rice fields, and agricultural fields based on their respective areas.